Reprogramming of tumor-associated macrophages by metabolites generated from tumor microenvironment - Seung Woo Kim; Chan Woo Kim; Young-Ah Moon; Hong Seok Kim (Animal Cells and Systems)
The tumor microenvironment comprises both tumor and non-tumor stromal cells, including tumor-associated macrophages (TAMs), endothelial cells, and carcinoma-associated fibroblasts. TAMs, major components of non-tumor stromal cells, play a crucial role in creating an immunosuppressive environment by releasing cytokines, chemokines, growth factors, and immune checkpoint proteins that inhibit T cell activity. During tumors develop, cancer cells release various mediators, including chemokines and metabolites, that recruit monocytes to infiltrate tumor tissues and subsequently induce an M2-like phenotype and tumor-promoting properties. Metabolites are often overlooked as metabolic waste or detoxification products but may contribute to TAM polarization. Furthermore, macrophages display a high degree of plasticity among immune cells in the tumor microenvironment, enabling them to either inhibit or facilitate cancer progression. Therefore, TAM-targeting has emerged as a promising strategy in tumor immunotherapy. This review provides an overview of multiple representative metabolites involved in TAM phenotypes, focusing on their role in pro-tumoral polarization of M2.